Khadicha Lake Of Region Bukhara Type of Phytoplankton - S.B. Bo’riyev; G.Z. Ochilova (Genius Journals, 2022)
The article provides information on the geographical location of Lake Khadija, the morphometric features of the lake, water supply, blue-green, green, diatoms and euglena representatives of phytoplankton found in the lake. In addition, the number of species in each section, the taxonomic analysis of the species, and the seasonal variation in the amount of phytoplankton with water temperature also contributed
Keywords: Collector; phytoplankton; blue-green; euglena